Ruthenium-enhanced curcumin derivatives target tumor growth and cancer-related inflammation in head and neck cancer models - Veselá, Kateřina; Tatar, Ameneh; Kejík, Zdeněk; Abramenko, Nikita; Kaplánek, Robert; Babula, Petr; Kučnirová, Kateřina; Hajduch, Jan; Martásek, Pavel; Jakubek, Milan (Frontiers in Oncology, 2025)
IntroductionHead and neck cancers (HNC) remain a significant clinical challenge, particularly due to their association with chronic inflammation triggered by tobacco carcinogens and human papillomavirus (HPV) infection. Persistent activation of proinflammatory and proangiogenic pathways, including nuclear factor kappa B (NF-kB), interleukin 6 (IL-6), and interleukin 8 (IL-8), plays a crucial role in tumor progression.MethodsIn this study, we synthetized ruthenium-enhanced curcumin derivatives (complexes 3 and 4) and study their anti-inflammatory and anticancer properties by using HNC cell lines.ResultsComplex 3 demonstrated potent cytotoxic and antiproliferative effects across both HPV-negative and HPV- positive HNC cell lines, while complex 4 showed selectivity toward oral squamous cell carcinoma (OSCC). Both complexes exhibited cytostatic and migrastatic activities. Importantly, treatment with these complexes significantly suppressed NF-kB activity and reduced IL-6 and IL-8 levels more effectively than native curcumin.DiscussionThese findings highlight their potential not only as stand-alone therapeutic agents but also as adjuvants in combination therapies for HNC.